Strategi Pengembangan Sistem Pengelolaan Agroforestri di Desa Karangsari Kecamatan Darma Kabupaten Kuningan - Zamila, Ailla; Nurlaila, Ai (Fakultas Kehutanan dan Lingkungan, Universitas Kuningan, 2023)
Karangsari Village is one of the villages that applies agroforestry in land management. Around 204 ha or 74% of the village area is agroforestry land and about 500 people of the total population are farmers. However, in its management there are various obstacles such as fluctuating prices or tending to fall during the harvest, pest and disease attacks and capital procurement. Some of these problems are common, but by conducting a SWOT analysis based on the strengths, weaknesses, opportunities and threats contained in the management of agroforestry in Karangsari Village, it is found that the ST (Strength Threat) strategy is a situation when facing various threats, but still has strengths from internal aspects. Several strategies were obtained: 1) implement a coordination system to determine market needs; 2) using organic fertilizer as an alternative material; 3) planting crops that are in high demand during a pandemic; 4) implementing the development of young agricultural entrepreneurs, 5) utilizing farmer groups as a forum for farmers to plan and deal with problems contained in management, 6) strengthen relationships between farmers and village officials so that there is good synergy, and 7) improve infrastructure development especially for road access. Karangsari Village is one of the villages that applies agroforestry in land management. Around 204 ha or 74% of the village area is agroforestry land and about 500 people of the total population are farmers. However, in its management there are various obstacles such as fluctuating prices or tending to fall during the harvest, pest and disease attacks and capital procurement. Some of these problems are common, but by conducting a SWOT analysis based on the strengths, weaknesses, opportunities and threats contained in the management of agroforestry in Karangsari Village, it is found that the ST (Strength Threat) strategy is a situation when facing various threats, but still has strengths from internal aspects. Several strategies were obtained: 1) implement a coordination system to determine market needs; 2) using organic fertilizer as an alternative material; 3) planting crops that are in high demand during a pandemic; 4) implementing the development of young agricultural entrepreneurs, 5) utilizing farmer groups as a forum for farmers to plan and deal with problems contained in management, 6) strengthen relationships between farmers and village officials so that there is good synergy, and 7) improve infrastructure development especially for road access.